1968
DOI: 10.1037/h0025354
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of behavioral styles between entering and graduating students in officer candidate school.

Abstract: 2 groups of students in an officer candidate school (N = 880) are compared to determine their differences in behavioral styles The instrument used is the Job Analysis and Interest Measurement. There is a difference at the .01 level of significance in the mean scores between entering (N = 561) and graduating (N = 319) students in 4 prechosen behavioral dimensions. Entering students compared with graduating students place a higher value on approval from others In the 3 other scales considered, the mean graduatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1972
1972
1984
1984

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Candidates who shifted their answers toward an active, aggressive coping style attained better class standings than those who did not shift. Using the Job Analysis and Interest Measure (JAIM), Petersen (1971) and Petersen and Lippitt (1968) found similar shifts of behavioral style within OCS. Petersen also found that behavioral style was related to success in OCS.…”
Section: Variables Relating To Performance During and After Ocsmentioning
confidence: 96%
“…Candidates who shifted their answers toward an active, aggressive coping style attained better class standings than those who did not shift. Using the Job Analysis and Interest Measure (JAIM), Petersen (1971) and Petersen and Lippitt (1968) found similar shifts of behavioral style within OCS. Petersen also found that behavioral style was related to success in OCS.…”
Section: Variables Relating To Performance During and After Ocsmentioning
confidence: 96%
“…For example, published reports available at that time (circa 1970) about several occupational groups that were carefully prescreened prior to entry-into-training revealed training-attrition rates ranging from 22% to 43%. Among these were attrition rates for Peace Corps volunteers (Gordon, 1967); nursing students in their first year of training (Katzell, 1968); nursing turnover in a teaching hospital (Saleh, Lee, and Brien, 1965); Army officer candidates during 23 weeks of training (Peterson and Lippitt, 1968); and naval aviation students (Bale and Ambler, 1971). …”
Section: Current Status Of Selection Standardsmentioning
confidence: 99%